2014
DOI: 10.1002/marc.201400217
|View full text |Cite
|
Sign up to set email alerts
|

Glucose‐Sensitive QCM‐Sensors Via Direct Surface RAFT Polymerization

Abstract: Thin, phenylboronic acid-containing polymer coatings are potentially attractive sensory layers for a range of glucose monitoring systems. This contribution presents the synthesis and properties of glucose-sensitive polymer brushes obtained via surface RAFT polymerization of 3-methacrylamido phenylboronic acid (MAPBA). This synthetic strategy is attractive since it allows the controlled growth of PMAPBA brushes with film thicknesses of up to 20 nm via direct polymerization of MAPBA without the need for addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 25 publications
0
38
0
Order By: Relevance
“…In particular, affinity sensors that use boronic acid (which forms boronate by binding to diol groups), including our current nanosensor (Figure S6), is in general not capable of distinguishing between different diol-containing monosaccharides. Although they may still be adequate for practical glucose detection in physiological fluids where glucose is present at dominant concentrations 32, 33 , we anticipate that it is possible to chemically modify boronic acid-based receptors to impart glucose-specificity to the nanosensor over other monosaccharides 34 , which will also be a major subject of our future investigation.…”
mentioning
confidence: 99%
“…In particular, affinity sensors that use boronic acid (which forms boronate by binding to diol groups), including our current nanosensor (Figure S6), is in general not capable of distinguishing between different diol-containing monosaccharides. Although they may still be adequate for practical glucose detection in physiological fluids where glucose is present at dominant concentrations 32, 33 , we anticipate that it is possible to chemically modify boronic acid-based receptors to impart glucose-specificity to the nanosensor over other monosaccharides 34 , which will also be a major subject of our future investigation.…”
mentioning
confidence: 99%
“…pH 8.5),16 yet is present at much lower concentrations in blood (typically around 10 µM).51 In previous QCM-D experiments with PBA-containing polymer brush films that were prepared via surface reversible addition fragmentation chain transfer polymerization (RAFT), we demonstrated that the frequency shifts observed for these polymer brush films upon exposure to 5 mM glucose were not affected by the presence of 10 µM fructose as a competing diol 40. PBA functionalized PMAA brush coated PPHF based glucose sensors.…”
mentioning
confidence: 83%
“…Although there are several methods involving the modification of various surfaces with BA-moieties allowing the creation of saccharide sensors using gold electrodes [78], quartz crystal microbalance (QCM) [79] and organic field transistor [80], these mostly use the polymer as a structural supporting matrix and will not be reviewed here. However, the previously discussed glucose-induced polymeric phase transition can be translated into a colorimetric or fluorescent signal by incorporating suitable dyes in the polymer chain that target one of the following three characteristic changes (Figure 8): (1) upon precipitation, the inside of the collapsed polymeric globule strongly dehydrates leading to a decrease in polarity; (2) in a one-phase system, the polymer tries to maximize its contact with the solvent, taking on a very open and extended polymer structure, mostly represented as a random coil, and, as a result of the phase transition, this structure becomes increasingly dense, decreasing the inter- and intra-distance between the polymer backbone and its side-chains; and (3) this dense polymeric structure also strongly hinders the mobility of the side-chains, which is sometimes referred to as an increase in local viscosity, preventing, for example, free rotation between conjugated aromatic rings.…”
Section: Sensory Applicationsmentioning
confidence: 99%